Israel and the Fundamental Question of Armenian Genocide Recognition - Minasyan, Edik; Gharibyan, Alik; Galstyan, Gayane (History and Culture, 2023)
This article aims to reevaluate and reassess as much as possible the principles of Israel’s policy regarding the recognition of the Armenian Genocide, its consequences, and the factors hindering the recognition. Particular emphasis is made on the development of Armenian-Israeli relations in the field of economic and technological cooperation. In the context of the geopolitical events that have taken place in recent years, the necessity of reinterpreting these relations in the region by increasing the role and influence of third countries is emphasized. Israel’s recognition of the Armenian Genocide has moral, political and civilizational importance from the point of view of developing relations between the two nations and establishing justice.